(untitled) (Tạp chí Y học Cộng đồng, 2025)
Objective: To describe the current status of the quality of life among former caregivers of patients with epilepsy at Nam Dinh Psychiatric Hospital. Subjects and Methods: The study population consisted of primary caregivers of patients with epilepsy. Study period: From June 2024 to December 2024. Study design: Cross-sectional descriptive study. Results:The majority of primary caregivers belonged to the age group over 60 years. The proportion of primary caregivers of patients with epilepsy reporting a high level of quality of life was 12.5%, while those reporting a low level was 39.1%. Conclusion: The proportion of primary caregivers of patients with epilepsy experiencing a low level of quality of life was relatively high at 39.1%.